Sukuk Negara Sebagai Alternatif Pembiayaan APBN di Indonesia - Nisak, Khoirun (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
The State Budget deficit that has continued for years has forced the government to find out an alternative debt financing other than foreign loans and the issuance of Government Bonds (SUN). In 2008 the government first issued Islamic Bonds (Sukuk Negara/SBSN) as an instrument for financing the budget deficit. After fourteen years, the number of issuance of Sukuk Negara/SBSN has increased every year with various different SBSN series. This research aims to known more about the mechanism for issuing Sukuk Negara and its implementation as an instrument for financing the budget deficit. This research uses a qualitative methodology. Through literature review in this research, it is known that Sukuk Negara have a major role in financing the State Budget deficit and to financing the development of government projects. The issuance of SBSN also plays a role in encouraging the growth of Islamic finance in Indonesia. Defisit APBN yang terus terjadi selama bertahun-tahun membuat pemerintah berupaya untuk mencari alternatif pembiayaan utang selain pinjaman luar negeri dan penerbitan Surat Utang Negara (SUN). Tahun 2008 pemerintah pertama kali menerbitkan Surat Berharga Syariah Negara (SBSN) sebagai instrumen pembiayaan defisit anggaran. Setelah berjalan empat belas tahun, jumlah penerbitan Sukuk Negara mengalami peningkatan setiap tahun dengan berbagai seri SBSN yang berbeda. Penelitian ini bertujuan untuk mengetahui lebih dalam mekanisme penerbitan Sukuk Negara dan implementasinya sebagai salah satu instrumen pembiayaan defisit anggaran. Penelitian ini menggunakan metodologi kualitatif. Melalui kajian literatur dalam penelitian ini diketahui bahwa Sukuk Negara memiliki peran besar dalam membiayai defisit APBN dan membiayai pembangunan proyek pemerintah. Penerbitan Sukuk Negara juga berperan dalam mendorong pertumbuhan keuangan syariah di Indonesia.